Mathematical Model of Adaptive Control of a Collaborative Mobile Manipulator in a Shared Working Environment - Yevsieiv, V. (My University, 2025)
This paper presents a mathematical model of adaptive control of a collaborative mobile manipulator in a shared working environment that meets the requirements of safe and effective human-robot interaction. The developed approach is based on an adaptive controller that provides accurate tracking of the desired trajectory even in the presence of parameter uncertainties. Numerical simulations have shown that the actual robot trajectory practically coincides with the given one, and the error does not exceed 0.05 rad and decreases asymptotically over time. In addition, the parametric adaptation system demonstrated a gradual approximation of the estimated parameter to the true one, which confirms the model's ability to self-learn in dynamic conditions. The results obtained indicate the high efficiency of the proposed method, its stability and prospects for implementation in the production processes of Industry 5.0.
Keywords: adaptive control; mobile manipulator; trajectory tracking; collaborative robotics